Firm characteristics and Biological Asset Disclosure on Agricultural Firms - Anita Carolina; Fariyana Kusumawati; Khy'sh Nusri Leapatra Chamalinda (Jurnal Akuntansi dan Keuangan, 2020)
Agriculture firms are facing challenges on applying the Statement of Financial Accounting Standards (PSAK) 69 which regulates the recognition, measurement, disclosure, presentation and reporting biological assets because of the unique trait of biological assets. This research aims to decide the factors that influence the biological asset disclosure by testing the effect of leverage, profitability, liquidity, firm’s growth, biological assets’ intensity, firm size, type of auditor, and listing status. The samples used in this research are the agriculture firms listed on the Indonesia Stock Exchange (IDX) between 2016 and 2018. The data are collected from the auditor financial statement. This research uses a quantitative method with multiple linear regression analysis. The conclusion is that the intensity of biological asset influences the biological asset disclosure, while leverage, profitability, liquidity, firm’s growth, firm size, type of auditor, and listing status do not influence the biological asset disclosure. This research contributes as literature for academics, gives knowledge about agriculture firm’s problems for the standard compiler, and improving the agriculture firms’ obediency in disclosing their biological asset following the PSAK 69